Aza-BODIPY-based Fluorescent and Colorimetric Sensors and Probes - Sonkaya, Ömer; Soylukan, Caner; Pamuk Algi, Melek; Algi, Fatih (Current Organic Synthesis, 2023)
Aza-boron-dipyrromethenes (Aza-BODIPYs) represent an important class of chromophores absorbing and emitting in the near-infrared (NIR) region. They have unique optical and electronic features and higher physiological and photo stability than other NIR dyes. Especially after the development of facile synthetic routes, Aza-BODIPYs have become indispensable fluors that can find various applications ranging from chemosensors, bioimaging, phototherapy, solar energy materials, photocatalysis, photon upconversion, lasers, and optoelectronics. Herein, we review Aza-BODIPY based fluorescent and colorimetric chemosensors. We show the potential and untapped toolbox of Aza-BODIPY based fluorescent and colorimetric chemosensors. Hence, we divide the fluorescent and colorimetric chemosensors and probes into five sections according to the target analytes. The first section begins with the chemosensors developed for pH. Next, we discuss Aza-BODIPY based ion sensors, including metal ions and anions. Finally, we present the chemosensors and probes concerning reactive oxygen (ROS) and nitrogen species (RNS) along with biologically relevant species in the last two sections. We believe that Aza-BODIPYs are still in their infancy, and they have a promising future for translation from the bench to real biomedical and materials science applications. After two decades of intensive research, it seems that there are many more to come in this already fertile field. Overall, we hope that future work will further expand the applications of Aza-BODIPY in many areas.
Keywords: fluorescence chemosensor